The development of vocational training systems for local government staff in West Africa - A comparative study between the systems of Burkina Faso, Mali and Niger in the light of the French and the German experiences. - (:unkn) unknown (My University, 2024)
Decentralization in West Africa is facing major challenges. Despite 20 to 30 years of intensified decentralization efforts, local authorities are still insufficiently equipped to carry out their missions and respond adequately to the needs of the population. In addition to the necessary financial and material resources, they are crucially lacking in qualified staff. To address this shortage of human resources, capacity building activities for decentralization stakeholders constitute a key element. This PhD thesis addresses the main aspects of the initial professional training of local government officials through a comparative study between Mali, Niger and Burkina Faso. The study also refers to experiences in professional training for the public sector from France and Germany. It becomes clear that training can only be successful if the design of the initial professional training system is consistent with the rules governing the careers of local civil servants as defined in local civil service law.
Keywords: African Research